1993
DOI: 10.1093/eurheartj/14.suppl_c.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin converting enzyme inhibition on endothelial vasodilator function in primary human hypertension

Abstract: KEY WORDS: Angiotensin-converting enzyme inhibition, cilazapril, endothelium, acetylcholine, forearm blood flow, hypertension

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…Patients in that study were being treated with a variety of antihypertensive medications, and most were not taking an ACE inhibitor. Our findings are also consistent with a preliminary report by Kiowski et al, 37 who reported that long-term treatment with the ACE inhibitor perindopril did not affect endothelium-dependent vasodilation of forearm resistance vessels of hypertensive patients. The findings, however, appear to conflict with those of Hirooka et al, 21 who reported that administration of a single dose of captopril, but not nifedipine, improved endothelium-dependent vasodilation in forearm resistance vessels of hypertensive patients.…”
Section: Effect Of Antihypertensive Treatmentsupporting
confidence: 94%
“…Patients in that study were being treated with a variety of antihypertensive medications, and most were not taking an ACE inhibitor. Our findings are also consistent with a preliminary report by Kiowski et al, 37 who reported that long-term treatment with the ACE inhibitor perindopril did not affect endothelium-dependent vasodilation of forearm resistance vessels of hypertensive patients. The findings, however, appear to conflict with those of Hirooka et al, 21 who reported that administration of a single dose of captopril, but not nifedipine, improved endothelium-dependent vasodilation in forearm resistance vessels of hypertensive patients.…”
Section: Effect Of Antihypertensive Treatmentsupporting
confidence: 94%
“…This has been observed in the abdominal aorta, carotid arteries or mesenteric vessels after treatment with hydralazine or reversal of the hypertensive stimulus. However, most of the human studies in which endothelial function has been assessed before and after normalization of hypertension with conventional therapy have not shown an improvement in the endothelial-dependent responses [12,28,29,31]. It seems, therefore, that endothelial dysfunction in human hypertension, once established, is more difficult to reverse than in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental question which remains unanswered is whether endothelial dysfunction in hypertension, if indeed present, is a cause or consequence of the condition. Whereas studies in hypercholesterolaemia have shown the reversal of endothelial dysfunction with effective treatment [26,27], this has not been consistently demonstrated in hypertension [11,12,[28][29][30][31]. The study of individuals who, although clinically normal, are at increased genetic risk for hypertension offers an alternative approach which avoids any confounding effects of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the forearm blood flow (FBF) response to intra-arterial infusion of vasodilator agents by venous occlusion plethysmography is the most widely used method in the study of EDV in the peripheral circulation in humans [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Human Forearm Modelmentioning
confidence: 99%
“…The defect response to L-NMMA observed in essential hypertensive patients has been found to be reversed by antihypertensive treatment [156], but one controlled randomized trial [157], two open treatment studies [158,159] and one observational study [160] failed to show that antihypertensive treatment improves EDV. However, four recently published studies showed that the ACE-inhibitors captopril [64] and lisinopril [161], as well as the Ca-channel blockers nifedipine [96] and lacidipine [162] improved EDV during long-term use, while no beneficial effect was seen with atenolol [96].…”
Section: Human Hypertensionmentioning
confidence: 99%